Genetically Downregulated Interleukin-6 Signaling Is Associated With a Favorable Cardiometabolic Profile: A Phenome-Wide Association Study. Issue 11 (16th March 2021) - Georgakis, Marios K.; Malik, Rainer; Li, Xue; Gill, Dipender; Levin, Michael G.; Vy, Ha My T.; Judy, Renae; Ritchie, Marylyn; Verma, Shefali S.; ,; Nadkarni, Girish N.; Damrauer, Scott M.; et al.
Abstract : Supplemental Digital Content is available in the text.